Tren Penelitian Tanah Longsor di Indonesia Rentang Tahun 2011-2021 Berdasarkan Analisis Bibliometrik - Meli Muchlian; Leli Honesti (Universitas Islam Raden Rahmat, Malang, 2023)
Indonesia has a high risk of landslides because climate and weather factors dominate more than 90%. This study aims to analyze the landslide topic in Indonesia using bibliometrically based on science and engineering fields. This research consists of three stages, namely (1) identification of research topics from the Google Scholar database; (2) software Processing; and (3) data analysis and interpretation. The study results show that bibliometric analysis can be used to analyze scientific works in landslide field research based on the classification adjusted to the keywords. The increasing number of landslide events in recent years is closely related to the development of information and the number of landslide research in science and engineering. With the exposure of keywords and co-citations related to the article, new topics are to be studied further as the development of research related to landslides.